2012
DOI: 10.3389/fonc.2012.00164
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1: from structure to cancer therapy

Abstract: Here, we review current evidence pointing to the function of VDAC1 in cell life and death, and highlight these functions in relation to cancer. Found at the outer mitochondrial membrane, VDAC1 assumes a crucial position in the cell, controlling the metabolic cross-talk between mitochondria and the rest of the cell. Moreover, its location at the boundary between the mitochondria and the cytosol enables VDAC1 to interact with proteins that mediate and regulate the integration of mitochondrial functions with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
198
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(201 citation statements)
references
References 437 publications
2
198
0
1
Order By: Relevance
“…Contrary to previously held beliefs, recent studies have demonstrated that mitochondria are also key players in the transformation process of cancer cells and may be used as targets for anticancer therapy (2)(3)(4)(5)(6). The involvement of mitochondria in cancer cell function could be linked to the enhanced accumulation of iron and reactive oxygen species (ROS) in mitochondria of cancer cells, which is thought to result from the increased metabolic and energetic demands of the transformed phenotype (7).…”
mentioning
confidence: 73%
“…Contrary to previously held beliefs, recent studies have demonstrated that mitochondria are also key players in the transformation process of cancer cells and may be used as targets for anticancer therapy (2)(3)(4)(5)(6). The involvement of mitochondria in cancer cell function could be linked to the enhanced accumulation of iron and reactive oxygen species (ROS) in mitochondria of cancer cells, which is thought to result from the increased metabolic and energetic demands of the transformed phenotype (7).…”
mentioning
confidence: 73%
“…Moreover, mitochondrial bioenergetics may also be modified by CBD via interaction with mitochondrial voltage-dependent anion channel 1 (VDAC1; see BIon Channels^) [84], which may affect the production of adenosine triphosphate (ATP). VDAC1 is involved in the transport of ions (e.g., calcium) and multiple metabolites, including adenosine diphosphate [85], the substrate of ATP. There are still some discrepancies surrounding the nature of CBD's action on the complexes comprising the ETC.…”
Section: Electron Transport Chainmentioning
confidence: 99%
“…Tajeddine N. et al reported that knockdown of the VDAC1 was able to inhibit cell death induced by cisplatin (Tajeddine et al, 2008). In addition, Arbel N. et al have demonstrated that direct interaction of anti-apoptotic Bcl-2 and Bcl-xL with VDAC results in decreased channel conductance and causes anti-apoptotic actions (Arbel et al, 2012).Thus, searching for compounds that block the binding of VDAC1 and prosurvival/antiapoptotic hexokinase (HK) and Bcl-2 family proteins may be promising targets for anticancer drug research (Shoshan-Barmatz and Mizrachi, 2012). Recently, Prezma T. et al have designed VDAC1-based cell-penetrating peptides which target HK, Bcl-2 and Bcl-xL to inhibit the interaction of VDAC1 and the anti-apoptotic proteins in B-cell CLL (Prezma et al, 2013).…”
Section: Dulanerminmentioning
confidence: 99%